Síntese e caracterização de matrizes híbridas para aplicação em sistemas de liberação controlada - Araújo, Helena Aparecida Guimarães Brito de [UNESP] (2015)
Carriers and flexible macromolecular chains covalently linked, hydrogels are highly hydrophilic polymers, and when synthesized from the junction of synthetic and natural polymers have excellent biocompatibility, biodegradability and porosity. What expands its applicability from controlled release of both drugs as nutrients to the soil, therapeutic implants, cell culture and cartilage, and others. In this work, nanocomposite hydrogels formed from polyacrylamide (PAAm), carboxymethylcellulose (CMC) and zeolite were synthesized via free radical polymerization. The characterizations of these nanocomposites were made from swelling degree studies in four different media (distilled water, NaCl (varying the concentration of 0.05; 0.10; 0, 15 and 0.20 mol / L), CaCl 2 (0.15 mol / L) and AlCl 3 (0.15 mol / L); kinetic properties (n and k); fourier transform infrared spectroscopy (FTIR); scanning electron microscopy (SEM) and thermal analysis (TG, DTG and DSC). It was possible to conclude that the PAAm, CMC and zeolite hydrogels had lower absorption capacity when compared to hydrogels without zeolite. Also, the concentration of N, N, N', N' - tetramethylethylenediamine TEMED catalyst has strong influence on the degree of swelling of hydrogels, because it acts directly on the speed and in the polymerization reactions. Saline solutions containing large ionic charges (CaCl 2 and AlCl 3 ) have lower performance in the swelling degree when compared to solutions with small charge (NaCl), being that its variation no provoked significant changes in the swelling degree. As seen in the FTIR, SEM and EDS techniques, there was interaction between hydrogels PAAm and CMC with the zeolite, decreasing the matrix pore sizes which directly influences the degree of swelling and structure of hydrogels. From thermal analysis, it was possible to conclude that the zeolite increased the thermal stability of nanocomposites. Thus ...